2007
DOI: 10.1111/j.1442-2050.2007.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative management of small cell carcinoma of esophagus

Abstract: Primary small cell carcinoma of the esophagus (SmCC) is an uncommon aggressive tumor characterized by early systemic dissemination and poor prognosis, regardless of the methods of treatment. The optimal treatment strategy remains uncertain. A retrospective study was conducted to review the results of non-operative treatment for patients with limited and metastatic esophageal SmCC. Between 1993 and 2003, 10 patients were diagnosed to have primary esophageal SmCC in our institution. Six of them had disseminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…However, in present study, patients have showed a median survival time of 22.4 months after radical esophagectomy and regional lymphadectomy with or without adjutant therapy for esophageal NEC. To our best knowledge, recently published studies with relatively large cases exploring the role of surgery in treating limited disease stage esophageal NEC have yield a median survival time of 10.1 to 28.5 months (9,16,(22)(23)(24), while patients treated with chemoradiotherapy alone yielded a median survival time of 8.0 to 16.1 months (25)(26)(27). Therefore, it seemed that surgery may benefit patients with limited stage esophageal NEC, but the role of surgery in treating esophageal NEC still remains to be confirmed and validated (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, in present study, patients have showed a median survival time of 22.4 months after radical esophagectomy and regional lymphadectomy with or without adjutant therapy for esophageal NEC. To our best knowledge, recently published studies with relatively large cases exploring the role of surgery in treating limited disease stage esophageal NEC have yield a median survival time of 10.1 to 28.5 months (9,16,(22)(23)(24), while patients treated with chemoradiotherapy alone yielded a median survival time of 8.0 to 16.1 months (25)(26)(27). Therefore, it seemed that surgery may benefit patients with limited stage esophageal NEC, but the role of surgery in treating esophageal NEC still remains to be confirmed and validated (28).…”
Section: Discussionmentioning
confidence: 99%
“…Because the frequency of esophageal small cell carcinoma is low, no standard treatment for esophageal small cell carcinoma has been established, and there are only limited reports of long-term survival. It remains controversial whether surgery is necessary, because chemotherapy plays a key role in the treatment for patients with esophageal small cell carcinoma [14]. Surgery may contribute to the long-term survival of patients without nodal metastasis, and patients with nodal metastasis have a better chance of long-term survival if the nodal metastasis is controlled or cured by chemotherapy or radiotherapy before surgery [15].…”
Section: Discussionmentioning
confidence: 99%
“…18 33 Yau, et al suggested that chemotherapy with radiotherapy should not be recommended as the primary treatment for SCCE until randomized trials have been performed. 3 In our case, CRT was performed according to a regimen for SCCL, using CDDP and VCR. We thought that surgery might prove too invasive, as the patient was 84 years old, although surgery has priority for achieving local control of SCCE.…”
Section: -3 8-9 13 16 19-20 21 24mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In addition, SCCE displays 26 Few reports of large series have been reported to date because of the rarity of this entity. Optimal treatment for this tumor has yet to be defined, because of the lack of any comprehensive description of SCCE, and surgery, chemotherapy, radiotherapy, or a combination might be performed empirically, with no promise of efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation